Efficacy and safety of Xijiao Dihuang decoction in treating Henoch-Schönlein purpura: Study protocol for systematic review. Issue 51 (23rd December 2021) - Kong, Zhiqian; Zheng, Jiaming; Wu, Junwei; Ou, Jianzhao; Zhou, Xinyu; Huang, Haiyan
Abstract: Background: Henoch-Schönlein purpura is one of the most common systemic vascular inflflammatory disease in childhood with purpuric rash, arthritis, renal involvement, and abdominal pain. As a treatment for it, Xijiao Dihuang decoction, a traditional herbal formula, has been used. The object of this systematic review and meta-analysis is to assess the effificacy and safety on Xijiao Dihuang decoction in treating allergic purpura. Methods: The following electronic databases will be systematically searched up to November 7, 2019 for eligible studies: The Cochrane Library, Embase, PubMed, Web of Science, the Chinese National Knowledge Infrastructure (CNKI), the Chinese Biomedical LiteratureDatabase (CBM), the Chinese Scientifific Journal Database (VIP), andtheWanfang Database. Thetreatment group in the included studies will receive both routine western medicines and Xijiao Dihuang decoction, while the control group will receive routine western medicines. Data extraction and risk of bias assessments will be conducted by 2 independent reviewers. Heterogeneity will be assessed by I2 statistics, while reporting bias will be evaluated by funnel plots and Begg and Egger test. Sensitivity analysis and Subgroup analysis will be performed when necessary. Review Manager software (RevManV.5.3.0) and Stata will be used for all statistical analyses. Ethics approval is not required as no privacy data were involved. This systematic review and meta analysis will be published in a peer-reviewed journal. Results: This study could provide a systematically evaluated therapeutic efficacy and safety of XJDHD on patients with HSP via including RCTs that matches the needs. And we also expect to find predictors of treatment through subgroup analysis, helping patients with HSP detect as well as cope with the disease as early as possible. Conclusion: The conclusion of our study will provide the systematical review of the efficacy and safety of XJDHD on patients with HSP, and provide predictors of treatment. PROSPERO registration number: PROSPERO CRD 42018111293